DESAIN DAN PEMBUATAN ALAT PEMBERSIH INJECTOR PORTABLE SEPEDA MOTOR BERBASIS FLASHER - Firdaus Hutasoit, Ricky Togu; Siregar, Ahmad Marabdi; Siregar, C A (Jurnal Pendidikan Vokasi Otomotif, 2023)
In the motorcycle system there is a component and the Electrical Full Injection System (EFI) of this Injector component functions to inject high-pressure fuel from the common rail according to the signal given by the ECU in a Tensioner contact state or the condition of the combustion chamber engine at Timin Injection optimum, the amount of fuel injection, fuel injection ratio and fogging conditions.Two-Way Electromagnetic controls the pressure in the chamber of the injector to control the start and finish of fuel injection.Orifice in the control chamber controls the angle of opening of the nozzle to control the ratio of fuel injection.Clogging of the nozzle holes causes the effect is that the acceleration power of the motorbike engine is decreasing. this makes it difficult for motorbikes to be operational again. After cleaning the dirt that clogs the injectors in the nozzle holes, making this tool can also extend the life of the injectors.Development is a process that is used to develop and investigate a product. The test results of this tool show that the injector cleaner works well. During testing with the Vario 125 motorbike, the injector misting produced +- 35 ml/minute. If an injector produces more than 15-20 ml/minute. Then the injector is still feasible to use and use.